Current Safety of Renal Allograft Biopsy With Indication in Adult Recipients: An Observational Study. Issue 6 (February 2016) - Tsai, Shang-Feng; Chen, Cheng-Hsu; Shu, Kuo-Hsiung; Cheng, Chi-Hung; Yu, Tung-Min; Chuang, Ya-Wen; Huang, Shih-Ting; Tsai, Jun-Li; Wu, Ming-Ju
Abstract : Abstract: Renal biopsy remains the golden standard diagnosis of renal function deterioration. The safety in native kidney biopsy is well defined. However, it is a different story in allograft kidney biopsy. We conduct this retrospective study to clarify the safety of allograft kidney biopsy with indication. All variables were grouped by the year of biopsy and they were compared by Mann–Whitney U test (for continuous variables) or Chi-square test (for categorical variables). We collected possible factors associated with complications, including age, gender, body weight, renal function, cause of uremia, status of coagulation, hepatitis, size of needle, and immunosuppressants. We recruited all renal transplant recipients undergoing allograft biopsy between January of 2009 and December of 2014. This is the largest database for allograft kidney biopsy with indication. Of all the 269 biopsies, there was no difference in occurrence among the total 14 complications (5.2%) over these 6 years. There were only 3 cases of hematomas (1.11%), 6 gross hematuria (2.23%), 1 hydronephrosis (0.37%), and 2 hemoglobin decline (0.74%). The outcome of this cohort is the best compared to all other studies, and it is even better than the allograft protocol kidney biopsy. Among all possible factors, patients with pathological report containing "medullary tissue only" were susceptible to complications ( P  < 0.001, 1.8 of relative risk). In modern era, this study demonstrates the safety of allograft kidney biopsy with indication. Identifying the renal capsule before biopsy to avoid puncture into medulla is the most important element to prevent complications.